DAYA SIMPAN BUAH MANGGIS (Garcinia mangostana L.) PADA BERBAGAI TINGKAT KETUAAN DAN SUHU PENYIMPANAN - Dondy Setyabudi; S. M Widayanti; Sulusi Prabawati (Jurnal Penelitian Pascapanen Pertanian, 2015)
The aim of research provides information physicochemical characters of three levels of maturity picking of mangosteen fruit in storage at both low and ambient storage temperature. Mangosteen fruit was obtained from production centers in villages Puspahiang, Puspahiang, Tasikmalaya and Wanayasa, Purwakarta, West Java. Sampling sites was used as block with twice sampling at each location. Mangosteen fruit picked at the three levels of stages of maturity detected by color; a) Maturity-1: green red spots, b) Maturity-2: breaker red”cumolat” 10-25%, and c) Maturity-3: 25-50% red-purple spots. The maturity was based on the color of the assumed age of farmers as picking at 106, 108, and 110 days after bloom (DAB). Further mangosteen fruit was stored at ambient temperature 27-29 °C and at low temperature 9 ± 1 °C. Observations were made on physical and chemical properties at intervals of 0, 3, 6 days, until the samples were not accepted by panelis. Analysis of physical properties include withered sepals, weight loss, skin color of fruit, and mangosteen rind characteristics using scanning electronic microscope/SEM. Meanwhile, the chemical properties include vitamin C, total acid, and total soluble solids. The results showed that the stage maturity 108 days (maturity-2 break color 10-25%) has a 12 day shelf life with characteristics withered sepals 2.61; weight loss of 3.80%; vitamin C 60.01 mg/100 g, total soluble solids 17.35%, and 0.41% total acid is the best stage picking compared to other stage picking. The maturity of the mangosteen fruit picking 108 days after blooming (maturity-2) with these characteristics was expected to be used for determining the proper maturity for picking suitable for export.